Analysis of Optimal RAP Content Based on Discrete Element Method. (20th June 2022) - Wang, Lei; Yang, Xiucheng
Abstract : Methods of recycling a large amount of waste asphalt mixture generated in pavement maintenance and decreasing the waste of existing resources are one of the problems that will be solved in the future. In this study, the mechanical parameters of asphalt mixture containing different amounts of RAP were analyzed by discrete element method (DEM), and the reasonable RAP content was discussed in combination with uniaxial compression test results. And it is considered that the contact between different particles will produce the failure of stress transfer between particles with different modulus, and the contact definition between RAP particles and virgin aggregate particles is added to make the discrete element model more in line with the actual situation. The results indicated that the trend of discrete element analysis was consistent with that of the uniaxial penetration test, but there were differences in the specific values. Uniaxial compression test results showed that the optimum RAP content of the recycled asphalt mixture was 30%. The optimal RAP content analysis result from the DEM simulation was smaller than the laboratory test result, and the theoretical optimal RAP content was 28%. The results of this study provide a reference for the mixture design of recycled asphalt mixture.